Tasks of Teachers to Work with Gifted Children - Nazirova Khilolakhon Mirzayakubovna (Peerian Journals Publishing, 2022)
This article is about gifted children and how they affect their development factors, the positive impact of information technology.
Keywords: talent; information technology; education; motive